c-Kit inhibitors for unresectable or metastatic mucosal, acral or chronically sun-damaged melanoma: a systematic review and one-arm meta-analysis - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Kohl, Christoph; Erdmann, Michael; Berking, Carola; Heppt, Markus (European Journal of Cancer, 2021)
Background: Activating genomic alterations of the receptor tyrosine kinase KIT are found preferentially in certain melanoma subtypes such as acral and mucosal melanoma or melanoma arising in chronically sun-damaged skin. However, the therapeutic value of c Kit inhibitors for these subtypes currently remains unclear. Objectives: The objective of this study was to summarise the efficacy and safety of c-Kit inhibitors for unresectable or metastatic mucosal, acral or chronically sun-damaged melanoma. Methods: We performed a systematic literature research in MEDLINE, Embase and CENTRAL and hand searched pertinent trial registers and conference abstracts for eligible trials until 23rd June 2020. Results were pooled using a random-effects model to calculate pooled proportions of objective response rates (ORRs) and severe adverse events (sAEs) from unselected KIT mutant or amplified cohorts. Results: Nineteen single-arm studies with an overall sample size of 601 patients were included. The studies investigated imatinib (n = 8), nilotinib (n = 7), dasatinib (n = 3) and sunitinib (n = 1). The pooled ORR for all inhibitors was 15% (95% confidence interval [CI]: 12-18%). Subgroup analysis revealed the highest ORR (20%; 95% CI: 14-26%) for nilotinib. The ORR for mucosal melanoma was 14% (95% CI: 6-24%) and 22% for acral lentiginous melanoma (95% CI: 14-30%). At least one sAE was reported in 42% of patients (95% CI: 34-50%). Conclusions: c-Kit inhibitors represent a valuable treatment option for patients with KIT mutant melanoma, in particular for mutations of exons 11 and 13. Furthermore, high-quality trials are urgently needed to investigate putative combinations of specific targeted therapies with immunotherapy. (c) 2021 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2021-10-15

Clinical determinants of long-term survival in metastatic uveal melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Erdmann, Michael; Heinzerling, Lucie; Hohberger, Bettina; Knorr, Harald; Leiter, Ulrike; Meier, Friedegund; Mohr, Peter; Rahimi, Farnaz; et al. (Cancer Immunology, Immunotherapy, 2021)
This study aimed to identify prognostic factors in patients with metastatic uveal melanoma (UM) that were associated with long-term survival in a real-world setting. A total of 94 patients with metastatic UM were included from German skin cancer centers and the German national skin cancer registry (ADOReg). Data were analyzed for the response to treatment, progression-free survival, and overall survival (OS). Prognostic factors were explored with univariate Cox regression, log-rank, and χ2-tests. Identified factors were subsequently validated after the population was divided into two cohorts of short-term survival (< 2 years OS, cohort A, n = 50) and long-term survival (> 2 years OS, cohort B, n = 44). A poor ECOG performance status (hazard ratio [HR] 2.0, 95% confidence interval [CI] 1.0–3.9) and elevated serum LDH (HR 2.0, 95% CI 1.0–3.8) were associated with a poor OS, whereas a good response to immune checkpoint blockade (ICB, p < 0.001), radiation therapy (p < 0.001), or liver-directed treatments (p = 0.01) were associated with a prolonged OS. Long-term survivors (cohort B) showed a higher median number of organs affected by metastasis (p < 0.001), while patients with liver metastases only were more common in cohort A (40% vs. 9%; p = 0.002). A partial response to ICB was observed in 16% (12/73), being 21% (8/38) for combined ICB, 17% (1/6) for single CTLA4 inhibition, and 10% (3/29) for single PD1 inhibition. One complete response occurred in cohort B with combined ICB. We conclude that the response to ICB and the presence of extrahepatic disease were favorable prognostic factors for long-term survival.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immune checkpoint blockade; Liver metastases; Liver-directed treatment; Long-term survival; Registry; Uveal melanoma

Clinical Prognostic Factors in metastatic Choroidal Melanoma - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, E.; Erdmann, Michael; Heinzerling, L.; Hohberger, Bettina; Knorr, H.; Leiter-Stoppke, U.; Meier, F.; Mohr, P.; Rahimi, F.; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Comparative efficacy analysis identifies immune checkpoint blockade as a new survival benchmark in advanced cutaneous squamous cell carcinoma - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Schatton, Tobias; Berking, Carola; Heppt, Markus (European Journal of Cancer, 2022)
Background: Cutaneous squamous cell carcinoma is a common type of skin cancer that may progress to locally advanced or metastatic disease. Both disease stages are managed by a variety of treatment options, including immune checkpoint blockade (ICB), targeted therapy to epidermal growth factor, chemotherapy or treatment combinations. However, the comparative efficacy of such treatments is unclear. Methods: We performed a systematic literature search of Medline, Embase and Central to identify eligible studies reporting Kaplan–Meier curves or individual patient data for overall survival (OS) or progression-free survival (PFS). Kaplan–Meier curves were digitised using the “‘WebPlotDigitizer” program. Individual patient data was subsequently remodelled and pooled for distinct treatment groups. Results: Overall, 22 independent studies were included of which n = 927 patients were evaluable for PFS and n = 1054 for OS. ICB showed the highest median PFS (mPFS 9.9 months (95% CI: 8.1–19.9)) and median OS (mOS not reached (95% CI: 31.5 months-not reached)) compared to chemotherapy (mPFS 3.0 months (95% CI: 2.2–4.8), mOS 12.6 months (95% CI: 9.6–15.8)), targeted therapy to epidermal growth factor (mPFS 4.9 months (95% CI: 4.4–5.6), mOS 12.7 months (95% CI: 11.9–14.9)) and combination therapies without ICB (mPFS 9.1 months (95% CI: 8.0–12.1), mOS 18.1 months (95% CI: 16.3–22.8)). The survival benchmark with ICB after 26 months for metastatic squamous cell carcinoma was 70.8% (95% CI: 61.5%–81.5%) versus 37.9% (95% CI: 29.5%–48.8%) for the combination group and 17.1% (95% CI: 9.5%–30.8%) for chemotherapy. Conclusion: ICB is superior to other systemic treatments and sets a novel survival benchmark for advanced cutaneous squamous cell carcinoma.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Cutaneous neoplasm; Cutaneous squamous cell carcinoma; Immune checkpoint blockade; Indirect comparison; Individual patient data; Overall survival; PD-1 therapy; Progression-free survival; Skin cancer

Efficacy of different Interventions for the Treatment of cutaneous Squamous Cell Carcinoma in situ (Bowen's Disease) - a systematic Literature Review and Meta-Analysis - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Evaluation of Long-term Clearance Rates of Interventions for Actinic Keratosis. A Systematic Review - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, Titus Josef; Schmitz, Lutz; Leiter, Ulrike; Garbe, Claus; Schöffski, Oliver; Berking, Carola; Heppt, M. V. (JAMA Dermatology, 2021)
Importance Multiple interventions are available for the treatment of actinic keratosis (AK). However, most randomized clinical trials and meta-analyses focus on short-term efficacy outcomes. Objective To investigate and synthesize the long-term efficacy (≥12 months) of interventions for AK from parallel-arm randomized clinical trials. Data Sources Searches in MEDLINE, Embase, and Central were conducted from inception until April 6, 2020. The reference lists of the included studies and pertinent trial registers were hand searched. The study was completed February 27, 2021. Study Selection Two reviewers screened the titles and abstracts of 2741 records. Finally, 17 published reports (original studies and follow-up reports) referring to 15 independent randomized clinical trials with an overall sample size of 4252 patients were included. Data Extraction and Synthesis Two reviewers independently extracted data on study, patient, and intervention characteristics. Network meta-analysis (NMA) of each outcome was conducted with a frequentist approach. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidance for NMA was used to assess the certainty of evidence. The revised Cochrane risk-of-bias tool for randomized clinical trials was used to evaluate the methodologic quality. Main Outcomes and Measures Participant complete clearance, participant partial clearance, and lesion-specific clearance were the outcomes, with each assessed at least 12 months after the end of treatment. Results Data from 15 independent randomized clinical trials including 4252 patients were extracted and synthesized. Ten studies were included in an NMA for the outcome of participant complete clearance, with photodynamic therapy with aminolevulinate (ALA-PDT) showing the most favorable risk ratio (RR) compared with placebo (RR, 8.06; 95% CI, 2.07-31.37; GRADE, moderate), followed by imiquimod, 5% (RR, 5.98; 95% CI, 2.26-15.84; GRADE, very low), photodynamic therapy with methyl aminolevulinate (MAL-PDT) (RR, 5.95; 95% CI, 1.21-29.41; GRADE, low), and cryosurgery (RR, 4.67; 95% CI, 1.36-16.66; GRADE, very low). Similarly, ALA-PDT had the highest RR in the NMA for lesion-specific clearance (RR, 5.08; 95% CI, 2.49-10.33; GRADE, moderate). No NMA was possible for participant partial clearance owing to poor reporting of this outcome. Conclusions and Relevance This systematic review and network meta-analysis found that therapy including ALA-PDT, imiquimod, 5%, MAL-PDT, and cryosurgery was associated with significant long-term efficacy in the NMA. This study provides data for a possible use in an evidence-based framework for selecting interventions with sustained lesion clearanc
CRIS-Team WoS Importer:2021-08-13

How to assess the efficacy of interventions for actinic keratosis? A review with a focus on long-term results - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Schmitz, Lutz; Dirschka, Thomas; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2021)
Actinic keratoses (AK) are common lesions of the skin caused by cumulative sun exposure. Since AK may progress to invasive cutaneous squamous cell carcinoma (cSCC), guidelines uniformly recommend early and consequent treatment. A variety of interventions are available; however, most randomized controlled trials, meta-analyses, and guidelines focus on outcomes that are usually evaluated 8–12 weeks after the end of treatment. Importantly, these assessments can capture the short-term, transient outcomes, but do not allow any conclusions about long-term results to be drawn and do not reflect the probability of transition towards cSCC. Until now, few studies have assessed the long-term results of interventions for AK. Indeed, finding the most appropriate end-point and adjunct time point for determining the long-term results of interventions for AK remains a challenge. Here, we provide an overview of the different ways of measuring the efficacy of AK treatments, such as using recurrence rates or sustained clearance rates, and discuss methodological aspects. Furthermore, we highlight the importance of evidence from post-marketing surveillance trials for the detection of efficacy values and safety signals. Additionally, we emphasize that a follow-up period of 12 months might not be sufficient to reflect the long-term results and stress the urgent need for a longer follow-up period and regular risk-stratified surveillance.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Actinic keratosis; Core outcomes; Follow-up; Long-term efficacy; Methodology; Prevention; Squamous cell carcinoma; Surveillance

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Patterns of Response and Survival According to the Presence of Hepatic and Extrahepatic Metastasis - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Hohberger, Bettina; Kaehler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; et al. (Cancers, 2021)
Simple Summary This retrospective multicenter study examines the influence of hepatic and extrahepatic metastases on the response of immune checkpoint blockade (ICB) in patients with metastatic uveal melanoma. A better response to dual ICB was observed in the presence of extrahepatic metastases in two recently published phase II trials. Therefore, we investigated two cohorts with and without extrahepatic metastasis and have assembled a population of 178 patients treated with ICB. The survival of this large cohort of patients with advanced UM was more favorable than that reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only. Background: Since there is no standardized and effective treatment for advanced uveal melanoma (UM), the prognosis is dismal once metastases develop. Due to the availability of immune checkpoint blockade (ICB) in the real-world setting, the prognosis of metastatic UM has improved. However, it is unclear how the presence of hepatic and extrahepatic metastasis impacts the response and survival after ICB. Methods: A total of 178 patients with metastatic UM treated with ICB were included in this analysis. Patients were recruited from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of hepatic metastasis, two cohorts were compared: patients with liver metastasis only (cohort A, n = 55) versus those with both liver and extra-hepatic metastasis (cohort B, n = 123). Data were analyzed in both cohorts for response to treatment, progression-free survival (PFS), and overall survival (OS). The survival and progression probabilities were calculated with the Kaplan-Meier method. Log-rank tests, chi(2) tests, and t-tests were performed to detect significant differences between both cohorts. Results: The median OS of the overall population was 16 months (95% CI 13.4-23.7) and the median PFS, 2.8 months (95% CI 2.5-3.0). The median OS was longer in cohort B than in cohort A (18.2 vs. 6.1 months; p = 0.071). The best objective response rate to dual ICB was 13.8% and to anti-PD-1 monotherapy 8.9% in the entire population. Patients with liver metastases only had a lower response to dual ICB, yet without significance (cohort A 8.7% vs. cohort B 16.7%; p = 0.45). Adverse events (AE) occurred in 41.6%. Severe AE were observed in 26.3% and evenly distributed between both cohorts. Conclusion: The survival of this large cohort of patients with advanced UM was more favorable than reported in previous benchmark studies. Patients with both hepatic and extrahepatic metastasis showed more favorable survival and higher response to dual ICB than those with hepatic metastasis only.
CRIS-Team WoS Importer:2021-07-23

Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Re-Induction following Resistance or Toxicity - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; et al. (Cancers, 2022)
Re-induction with immune checkpoint blockade (ICB) needs to be considered in many patients with uveal melanoma (UM) due to limited systemic treatment options. Here, we provide hitherto the first analysis of ICB re-induction in UM. A total of 177 patients with metastatic UM treated with ICB were included from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of ICB re-induction, two cohorts were compared: patients who received at least one ICB re-induction (cohort A, n = 52) versus those who received only one treatment line of ICB (cohort B, n = 125). In cohort A, a transient benefit of overall survival (OS) was observed at 6 and 12 months after the treatment start of ICB. There was no significant difference in OS between both groups (p = 0.1) with a median OS of 16.2 months (cohort A, 95% CI: 11.1–23.8) versus 9.4 months (cohort B, 95% CI: 6.1–14.9). Patients receiving re-induction of ICB (cohort A) had similar response rates compared to those receiving ICB once. Re-induction of ICB may yield a clinical benefit for a small subgroup of patients even after resistance or development of toxicities.
CRIS-Team Scopus Importer:2022-01-28
Keywords: CTLA-4; Immune checkpoint blockade; PD-1; Re-induction; Toxicity; Treatment resistance; Uveal melanoma

Is tebentafusp superior to combined immune checkpoint blockade and other systemic treatments in metastatic uveal melanoma? A comparative efficacy analysis with population adjustment - Petzold, Anne; Steeb, Theresa; Wessely, Anja; Koch, Elias; Vera, Julio; Berking, Carola; Heppt, Markus (Cancer Treatment Reviews, 2023)
Background: Distinct systemic treatments exist for metastatic uveal melanoma. Tebentafusp and combined immune checkpoint blockade (ICB) with ipilimumab plus anti-PD-1 antibodies are the most commonly used treatment options but their comparative efficacy is unclear. The aim of this study is to compare currently available systemic treatments regarding overall survival (OS) and progression-free survival (PFS) with a focus on the comparison of tebentafusp versus combined ICB. Methods: The protocol for this study was defined a priori and registered online in the PROSPERO international prospective register of systematic reviews (CRD42022308356, date of registration: 7.2.2022). We performed a systematic literature search in Medline, Embase, and Central to identify eligible studies reporting Kaplan-Meier curves or individual-level survival data showing OS and PFS for metastatic uveal melanoma patients treated with systemic treatments. Kaplan-Meier curves were digitized using the “WebPlotDigitizer” program. Individual-level survival data were subsequently remodelled and pooled for distinct treatment groups. To compare the OS of tebentafusp versus combined ICB, we used matching-adjusted indirect comparison (MAIC), two-stage MAIC (2SMAIC), and simulated treatment comparison (STC) together with digitized individual-level survival data as population-adjusted models. Results: Overall, 55 independent studies were included of which 2,682 patients were evaluable for OS and 2,258 for PFS. Tebentafusp showed the highest median OS (mOS) of 22.4 months (95% confidence interval (CI): 19.9–29.6) compared to combined ICB (mOS: 15.7 months (95% CI: 14.4–17.9)), anti-PD-(L)1 antibody (mOS: 10.9 months (95% CI: 9.8–13.4)), chemotherapy (mOS: 9.95 months (95% CI: 8.9–11.2)), targeted therapies (mOS: 8.86 months (95% CI: 7.5–10.8)), and anti-CTLA-4 antibody (mOS: 7.8 months (95% CI: 6.8–9.3). The median PFS (mPFS) was similar among the treatment groups ranging from 2.7 months to 3.4 months. For the comparison of tebentafusp versus combined ICB, the hazard ratio (HR) was 0.641 (95% CI: 0.449–0.915) in the unadjusted model, whereas the population-adjusted models showed a HR of 0.386 (95% CI: 0.236–0.631) using MAIC, 0.378 (95% CI: 0.234–0.612) applying 2SMAIC and 0.284 (95% CI: 0.184–0.440) using STC. Conclusions: Tebentafusp achieved the best results compared to combined ICB and other systemic treatments, although these results have to be interpreted with caution due to the approximative methodical approach and high heterogeneity of included studies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Immune checkpoint blockade; Individual patient data; Population-adjusted models; Survival; Tebentafusp; Uveal melanoma

Liver-directed treatment is associated with improved survival and increased response to immune checkpoint blockade in metastatic uveal melanoma: results from a retrospective multicenter trial - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Eckstein, Markus; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; Loquai, Carmen; et al. (Frontiers of Medicine, 2023)
Metastases of uveal melanoma (UM) spread predominantly to the liver. Due to low response rates to systemic therapies, liver-directed therapies (LDT) are commonly used for tumor control. The impact of LDT on the response to systemic treatment is unknown. A total of 182 patients with metastatic UM treated with immune checkpoint blockade (ICB) were included in this analysis. Patients were recruited from prospective skin cancer centers and the German national skin cancer registry (ADOReg) of the German Dermatologic Cooperative Oncology Group (DeCOG). Two cohorts were compared: patients with LDT (cohort A, n = 78) versus those without LDT (cohort B, n = 104). Data were analyzed for response to treatment, progression-free survival (PFS), and overall survival (OS). The median OS was significantly longer in cohort A than in cohort B (20.1 vs. 13.8 months; P = 0.0016) and a trend towards improved PFS was observed for cohort A (3.0 vs. 2.5 months; P = 0.054). The objective response rate to any ICB (16.7% vs. 3.8%, P = 0.0073) and combined ICB (14.1% vs. 4.5%, P = 0.017) was more favorable in cohort A. Our data suggest that the combination of LDT with ICB may be associated with a survival benefit and higher treatment response to ICB in patients with metastatic UM.
CRIS-Team Scopus Importer:2023-07-21
Keywords: anti-CTLA-4; anti-PD-1; immune checkpoint blockade; liver-directed therapy; SIRT; uveal melanoma

Long-term Effectiveness of Interventions for actinic Keratoses: Results of a systematic Review and Network Meta-Analysis - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, T.; Schmitz, L.; Lei-Ter-Stoppke, U.; Garbe, C.; Schöffski, Oliver; Berking, Carola; Heppt, Markus (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Long-term recurrence rates of actinic keratosis: A systematic review and pooled analysis of randomized controlled trials - Steeb, Theresa; Wessely, Anja; Petzold, Anne; Brinker, Titus J.; Schmitz, Lutz; Schöffski, Oliver; Berking, Carola; Heppt, Markus (Journal of the American Academy of Dermatology, 2021)
CRIS-Team Scopus Importer:2021-06-18

Spontaneous regression rates of actinic keratosis: a systematic review and pooled analysis of randomized controlled trials. - Steeb, Theresa; Petzold, Anne; Hornung, Annkathrin; Wessely, Anja; Berking, Carola; Heppt, Markus (Scientific Reports, 2022)
Actinic keratosis (AK) are precancerous lesions of the skin which may progress to invasive squamous cell carcinoma. However, single lesions may also persist or even regress and heal spontaneously. Until now, evidence on the natural course of AK including spontaneous regression is limited. We aimed to synthesize regression rates of AK. We performed a systematic literature research in Medline, Embase, and CENTRAL for eligible trials until 3rd March 2020. Spontaneous regression rates were pooled using a random-effects model to calculate pooled proportions of participant-specific and lesion-specific complete clearance rates reported for the placebo arms of randomized controlled trials. Subgroup analyses were performed to dissect differences according to the type of placebo, immunocompetence of the participants, and localization of the lesions. Data from 38 records was included. The pooled participant-specific clearance rate was 8% (95% CI 6-10%, I2 = 71%) while the lesion-specific clearance rate was 23% (95% CI 16-31%, I2 = 97%). The highest participant- and lesion-specific clearance rates were achieved 12 weeks after the end of treatment (12% and 33%, respectively). Subgroup analysis revealed participant- as well as lesion-specific clearance rates of 0% for organ transplant recipients (OTR). We conclude that only a few participants achieve complete regression of their AK without any active treatment. Besides, the results underline that lesion clearance without active treatment is unlikely in OTR. Thus, early and consequent treatment of AK is recommended. Special attention should be paid when treating AK of OTR.
EVALuna2:502113

The need for regular training in skin cancer screening: a cross-sectional study among general practitioners in Germany - Steeb, Theresa; Reinhardt, Lydia; Strasser, C.; Wessely, Anja; Schelling, J.; Petzold, Anne; Heppt, Markus; Meier, Friedegund; Berking, Carola (Journal of the European Academy of Dermatology and Venereology, 2022)
CRIS-Team Scopus Importer:2022-07-15

The quality of national skin cancer screening from the perspective of general practitioners: A questionnaire-based comparison between Saxony and Bavaria (SaBaScreen) - Strasser, C.; Reinhardt, L.; Steeb, Theresa; Wessely, Anja; Schelling, Jörg; Petzold, Anne; Heppt, Markus; Meier, F.; Berking, Carola (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Threshold Optimization for Tumor Markers S100b and MIA in Uveal Melanoma - A Single Center Analysis - Glaser, Naemi; Petzold, Anne; Wessely, Anja; Kaufmann, Matthias; Koch, Elias; Knorr, Harald; Voskens, Caroline; Heppt, Markus; Berking, Carola; Erdmann, Michael (Anticancer Research, 2023)
Background/Aim: Uveal melanoma (UM) is the most common malignant tumor of the eye in adults. Metastases develop in 50% of the patients, predominantly in the liver. In UM, the cut-off concentrations of the bloodbased tumor markers S100b and MIA are inconclusive. Patients and Methods: In this retrospective monocenter study, we statistically evaluated 1,878 S100b and 1,768 MIA measurements in 244 patients with UM from 2011-2020. Threshold optimization was performed using receiver operating characteristic (ROC) curves. Results: A total of 171 patients with non-metastatic UM (nmUM) and 73 patients with metastatic UM (mUM) showed no differences in sex, age at diagnosis or the affected eye. In mUM, 80% of the patients developed metastases to the liver at a median of 46 months after initial diagnosis. The sensitivity and specificity of S100b was 16.10% and 94.52%, and that of MIA was 31.86% and 81.42%, respectively. ROC curves revealed poor values for the area under the curve of 0.57 for S100b and 0.55 for MIA. The optimal cut-off concentration to detect metastases was 0.14 μg/l for S100b and 17.4 ng/ml for MIA. With at least one tumor marker elevated, optimized sensitivity was 20.40% and specificity 96.76%. Conclusion: Current thresholds for S100b and MIA in UM are not able to detect early metastatic disease and require additional diagnostics to clarify false positive results. Threshold optimization considering both S100b and MIA results in a better diagnostic validity with an acceptable specificity and a poor sensitivity. Highly sensitive blood-based and imaging methods to detect metastases early in UM are urgently needed.
CRIS-Team Scopus Importer:2023-11-03
Keywords: MIA; S100b; threshold optimization; tumor marker; Uveal melanoma